2017
DOI: 10.1109/tns.2017.2655579
|View full text |Cite
|
Sign up to set email alerts
|

Gamma and Electron NIEL Dependence of Irradiated GaAs

Abstract: In GaAs material, the radiation-induced degradations are demonstrated to vary according to the Non Ionizing Energy Loss (NIEL). But some discrepancies are still observed between experimental degradation measurements and predicted NIELs. The used displacement threshold energy (T d ) varies, from one author to another, from 10 eV up to 25 eV. A measurement made with 60 Co gamma rays is used to investigate the relevance of the NIEL scaling law for both electrons and gamma rays. A T d value of 21 eV is found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…These secondary electrons are slowed down by shielding before they leave to produce displacement damage in the active region of the device. In order to calculate the NIEL of 60 Co gamma rays ( 60 Co NIELγ) we have to integrate the slowed down spectrum of secondary electrons with the amount of atomic displacements produced by these secondary electrons (i.e., the electrons NIEL), the gamma NIEL is expressed as [18].…”
Section: IImentioning
confidence: 99%
See 2 more Smart Citations
“…These secondary electrons are slowed down by shielding before they leave to produce displacement damage in the active region of the device. In order to calculate the NIEL of 60 Co gamma rays ( 60 Co NIELγ) we have to integrate the slowed down spectrum of secondary electrons with the amount of atomic displacements produced by these secondary electrons (i.e., the electrons NIEL), the gamma NIEL is expressed as [18].…”
Section: IImentioning
confidence: 99%
“…This slowed down spectrum can vary, if a device or tested material is surrounded by heavy materials, and also depends on the thickness of such materials. It has been reported that the difference in equilibrium spectra between lighter materials and heavy materials could be up to 40% [18]. [11].…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation
“…There are various T d values reported in the literature according to varying defect levels introduced in the semiconductor band gap [17][18][19]. In the recent work of El Allam et al [20], discrepancies throughout literature are summarized concerning the scaling of experimental GaAs data with NIEL. Their work highlights that a value of threshold energy for atomic displacement in the range of 15-21 eV is best suited to fit experimental degradation measurements for many GaAs data.…”
Section: Introductionmentioning
confidence: 99%
“…The Compton electrons scattered during the interaction of γrays with matter can also induce displacement damage. The displacement damage dose generated by these Compton electrons was calculated using a NIEL value provided in [21]. In this reference the NIEL of 60 Co γ-rays have been calculated for GaAs.…”
Section: Niel Calculationsmentioning
confidence: 99%